A ética filosófica em Tomás de Aquino - Campos, Sávio Laet de Barros (2016)
The purpose of this work is to show the existence of a philosophical ethics in the midst of moral theology of Thomas Aquinas, in its most finished formulation, namely II.nd part of the Summa Theologiae. We believe that, commenting on the Nicomachean Ethics of Aristotle in the same period that began the composition of the II.nd part of the Summa Theologiae, and based on the axiom the grace does not suppress nature, but perfects it, Aquinas has left an eloquent testimony that did not seek to suppress the ethics of Stagirite, but integrate it into their personal theological synthesis. So we think exist in Thomas — within your moral theology — a philosophical ethics. Thus, we take this opportunity to show how this ethic can be offered to all men.